The adoption of good manufacturing practices in grain elevators - Velasquez, Sarah Elspeth (Kansas State University, 2007)
With increased focus on food safety and protection, the Food & Drug Administration (FDA) has examined the possibility of removing the exemption for elevators pertaining to Good Manufacturing Practices (GMPs). The objective of this thesis was to determine the extent to which Kansas Elevators have adopted GMPs. To accomplish the objective of this thesis, information from an online survey completed by 42 elevators was summarized and analyzed. The information that was collected focused on the general classification of the elevators, grain safety programs, pest control programs and procedures, operational methods and personal practices, and maintenance of the facilities and equipment. Correlation coefficients were computed to determine if there were any significant correlations between elevator characteristics and GMPs. The study found that many of the elevators surveyed do not comply with the GMP requirements, and would require more resources in order to do so. Little connection was made between classification information such as size, location, or number of employees and GMP implementation. The significant correlations found were between HACCP and Pest Management, and HACCP and Traceability. The main limitation of this thesis was the small number of survey participants.
Keywords: HACCP; GMP; Grain Elevator; Traceability; Implementation; Agriculture, General (0473); Economics, General (0501); Economics, Theory (0511)